Giottus Pictor Band 1: Giottos Leben - Schwarz, Michael Viktor (2004)
Giotto is considered to be the artist who framed the transition from the art of the middle ages to that of the modern era. From the perspective of cultural history, one may say: He was among those who shaped the language of early modern visual media. As a consequence, in historic memory he became a mythical figure. This figure assumed its accepted form in the mid 16th Century (Vasari). The goal of the book is to reveal as much historical reality as possible behind the myth. For this purpose a campaign was carried out in the Florentine State's Archive which brought to light ca. 100 hitherto unknown primary documents concerning the painter's life, family, and business. They are presented and discussed along with the ca. 50 primary documents which were already known. Besides that all texts from the 14th to the 16th Century are presented which contributed to Vasari's Giotto-figure. On the one hand, essential parts of Giotto's biography are reconstructed in this material. On the other hand, it explains the discourse which led to the Renaissance Image of Giotto. The book is the first volume of a monograph which will have three volumes. The second will be dedicated to Giotto's works, and the third to his afterlife. These parts will also deal with the material presented in the first volume, and it will be discussed under new perspectives.